Nilai-Nilai Kreativitas Siswa dalam Karya Gambar Ekspresi Tema Keluarga di Sekolah Dasar - Wulansih, Cintya Ayu; Fajrie, Nur; Setiawaty, Rani (JPKS (Jurnal Pendidikan dan Kajian Seni), 2025)
This research aims to analyze works of expression drawings on family themes and analyze the creative values of students in class IV elementary school. This research was conducted in Class IV of SDN 1 Sadang, Jekulo District, Kudus Regency, Central Java. The method used in this research is an exploratory qualitative approach. Data collection techniques were carried out using interviews, observation and documentation. Data analysis in this research uses Miles and Huberman's theory, including data reduction, data presentation and conclusion verification. Based on the results of the research, it was found that (1) Analysis of students' expressive drawings on family themes includes: (a) Utilization of surrounding objects, (b) Expression in the drawing, (c) Neatness of the drawing, (d) Completeness of the drawing object, and (e) Color composition. (2) Analysis of students' creative values in drawing expressions of family themes including: (a) Curiosity, (b) Ideas and suggestions (c) Appreciation of beauty, (d) Ability to work independently, and (e) Desire to try new things. With the right guidance, students' creativity can continue to be developed to improve their creative thinking and aesthetic skills.